2014
DOI: 10.1111/acer.12519
|View full text |Cite
|
Sign up to set email alerts
|

Oral Self‐Administration of EtOH: Sex‐Dependent Modulation by Running Wheel Access in C57BL/6J Mice

Abstract: Background The effects of stress, including neuroendocrine and behavioral sequelae aimed at maintaining homeostasis, are associated with increased alcohol consumption. Because both stress and drinking are multifactorial, the mechanisms underlying the relationship are difficult to elucidate. We therefore employed an animal model investigating the influence of blocked access to a running wheel on drinking in C57BL/6J (B6) mice. Methods In the first experiment, naïve, adult male and female subjects were individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…Our previous investigation of the effect of restricted wheel access on drinking (Piza-Palma et al, 2014) showed that female but not male B6 mice increased alcohol consumption in response to the stressor, and therefore we did not include males in the present study. However, it remains possible that low β-endorphin would also shift the reward sensitivity curve in male mice in this experimental context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous investigation of the effect of restricted wheel access on drinking (Piza-Palma et al, 2014) showed that female but not male B6 mice increased alcohol consumption in response to the stressor, and therefore we did not include males in the present study. However, it remains possible that low β-endorphin would also shift the reward sensitivity curve in male mice in this experimental context.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to better understand the complex interactions between stress and ethanol have frequently employed animal models (Crabbe, 2014), and these strategies have helped to identify some of the specific mechanisms contributing to aspects of the paradoxical relationship, especially as they pertain to the dependent state (Becker, Lopez, & Doremus-Fitzwater, 2011; Crabbe, Phillips, & Belknap, 2010). Our lab has employed intermittent interruptions of access to a running wheel as a model of stress (Ehringer, Hoft, & Zunhammer, 2009; Piza-Palma et al, 2014). We have argued that blocking access to a running wheel in the home cage induces frustration stress, and that this manipulation may be relevant to the human condition where stressors often involve loss of something desired, such as a loved one, health, or job (Thoits, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies in rodents have provided evidence for an interaction between voluntary wheel running and alcohol consumption . In a recent review, Hallgreen et al pointed out that, “physical exercise is widely regarded as “medicine” for the prevention and treatment of myriad somatic health conditions.” However, the effectiveness of physical activity to treat AUDs remains understudied.…”
Section: Behavioral Models Investigating the Interaction Between Wheementioning
confidence: 99%